The Effect of Financial Distress and Corporate Governance on the Discretionary Allowance for Impairment Losses - Wendy Tandiawan (Penerbit Goodwood, 2023)
Purpose: This study provides a more accurate picture of how financial distress and corporate governance influence managerial discretion, where the target of this research is the banking industry which is the industry with the largest financial assets. Companies that have large financial assets also have large allowances for impairment losses, and this is the main factor driving accrual-based company profits. This research activity is expected to provide scientific and practical benefits as well as a new view on financial distress, corporate governance and managerial discretion. For the banking industry, it provides an understanding of whether the recognition of allowance for impairment losses can be affected by financial distress and/or corporate governance. Method: This research uses a multiple linear regression with quantitative data. The sample selection in this study was carried out using a purposive sampling method, which is a sampling method that applies certain criteria according to the research objectives. The population in this study are companies in the banking industry that are listed on the Indonesian Stock Exchange. In this study, five years of observation were carried out from 2017 to 2021. Result: Based on the results of this study, it can be concluded that financial distress, institutional ownership, proportion of independent commissioners, and proportion of audit committee have no effect on managerial discretion. It refutes the hypotheses regarding the influence of financial distress and corporate governance on managerial discretion over the recognition of allowance for impairment losses. However, the managerial ownership has a positive influence on managerial discretion, which raises a possibility that managers who own shares of a company have a desire to get more benefits from the cost of equity and/or capital gains.